Maharashtra Anaemia Study: an investigation of factors associated with adolescent health and pregnancy-related outcomes in women from Maharashtra State, India - Ahankari, A.S. (2017)
Maharashtra Anaemia study (MAS) was conducted as a part of the PhD programme of Dr Anand Ahankari through a joint collaboration of the University of Nottingham, UK and Halo Medical Foundation, India. The main goal of the study was to establish baseline epidemiological data for anaemia research in pregnant women and adolescent girls in Maharashtra state of India. Iron deficiency anaemia is the most common form of anaemia observed in India, and assessed based on haemoglobin (Hb) levels in blood. Clinically, anaemia is categorised in mild, moderate and severe form based on Hb levels.